2006
DOI: 10.1111/j.1365-294x.2006.02903.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of heterozygosity on survival and hookworm resistance in California sea lion pups

Abstract: Low genetic heterozygosity is associated with loss of fitness in many natural populations. However, it remains unclear whether the mechanism is related to general (i.e. inbreeding) or local effects, in particular from a subset of loci lying close to genes under balancing selection. Here we analyse involving heterozygosity-fitness correlations on neonatal survival of California sea lions and on susceptibility to hookworm (Uncinaria spp.) infection, the single most important cause of pup mortality. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 64 publications
3
95
5
Order By: Relevance
“…Local effects have been increasingly implicated in HFCs (e.g. Hansson et al 2001;Acevedo-Whitehouse et al 2006;Lieutenant-Gosselin & Bernatchez 2006;von Hardenberg et al 2007).While it might seemsurprising that many studies have chosen markers that just happen to be in LD with the fitnesstraitunderinvestigation,recentempiricalstudieshave shown that LD can extend over many hundreds of kilobases, and be maintained for hundreds of generations (Laan & Pääbo 1997;Wright et al 1999;Reich et al 2001;Nordborg & Tavaré 2002;Hansson et al 2004; although see also Bierne et al2000;Dunning et al2000;Edwards&Dillon2004).…”
Section: A Brief Review Of Hypotheses Explaining Heterozygosityfitnesmentioning
confidence: 99%
See 1 more Smart Citation
“…Local effects have been increasingly implicated in HFCs (e.g. Hansson et al 2001;Acevedo-Whitehouse et al 2006;Lieutenant-Gosselin & Bernatchez 2006;von Hardenberg et al 2007).While it might seemsurprising that many studies have chosen markers that just happen to be in LD with the fitnesstraitunderinvestigation,recentempiricalstudieshave shown that LD can extend over many hundreds of kilobases, and be maintained for hundreds of generations (Laan & Pääbo 1997;Wright et al 1999;Reich et al 2001;Nordborg & Tavaré 2002;Hansson et al 2004; although see also Bierne et al2000;Dunning et al2000;Edwards&Dillon2004).…”
Section: A Brief Review Of Hypotheses Explaining Heterozygosityfitnesmentioning
confidence: 99%
“…Testing for local effects by regressing each individual marker with fitness is becoming standard practice; such tests are valuable in allowing us to understand the mechanisms underlying HFCs, and may also allow future identification of functionally important loci (e.g. Acevedo-Whitehouse et al 2006;Luikart et al 2008). However, caution must be exercised here: such multiple tests for significance will result in spurious significant results unless authors are careful to adjust the critical a level and thus guard against inflated type I errors (Simes 1986;Aiken & West 1991).…”
Section: Does Demographic History Influence the Strength Of Hfcs?mentioning
confidence: 99%
“…Inbreeding and reduced levels of genetic diversity have been found to negatively impact different components of fitness, including reproductive performance (Ortego et al., 2009; Seddon, Amos, Mulder, & Tobias, 2004), resistance to parasites (Acevedo‐Whitehouse et al., 2006; Hawley, Sydenstricker, Kollias, & Dhondt, 2005), and survival (Keller, Grant, Grant, & Petren, 2002; Olano‐Marin, Mueller, & Kempenaers, 2011a). The positive association between individual genetic diversity and fitness‐related traits arises when homozygotes are less fit than heterozygotes due to either heterozygote advantage (i.e., overdominance) or recessivity of deleterious or partly deleterious alleles (Charlesworth & Charlesworth, 1987; Keller & Waller, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, California sea lion hosts with enteritis have been found to have hookworm adults deep within muscle layers of the intestine and numerous nematodes free in the peritoneal cavity (Spraker et al, 2004(Spraker et al, , 2007Lyons et al, 2005). Hookworm disease in pinnipeds appears to be influenced by host genetics, with homozygosity at a single locus predisposing California sea lion hosts to hookworm anaemia (Acevedo-Whitehouse et al, 2006, 2009). In contrast, genetic studies of different pinniped species offer conflicting results concerning whether increased average homozygosity of hosts is correlated with increased hookworm disease (Acevedo-Whitehouse et al, 2006, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Hookworm disease in pinnipeds appears to be influenced by host genetics, with homozygosity at a single locus predisposing California sea lion hosts to hookworm anaemia (Acevedo-Whitehouse et al, 2006, 2009). In contrast, genetic studies of different pinniped species offer conflicting results concerning whether increased average homozygosity of hosts is correlated with increased hookworm disease (Acevedo-Whitehouse et al, 2006, 2009. Differences in host responses to hookworms owing to variations in host genetics may help explain the poor predictive value of hookworm infection intensity for pathogenicity and pup condition in certain studies (Lyons et al, 1997(Lyons et al, , 2001(Lyons et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%